THE ROLE OF DIGITAL MARKETING IN INCREASING CONSUMER PURCHASING DECISIONS: A LITERATURE REVIEW - Maikel Rudianto (CV. ADIBA AISHA AMIRA, 2025)
This research aims to examine the role of digital marketing in improving consumer purchasing decisions based on a literature review. Digital marketing, which includes the use of social media, websites, email, and e-commerce platforms, has become the main strategy for companies to reach consumers more widely, quickly, and personally in the digital era. The results show that digital marketing has a positive and significant eflect on consumer purchasing decisions. This influence is reflected through easy access to information, direct interaction between brands and consumers, and reviews and recommendations from other users that strengthen consumer trust. In addition, message personalisation and attractive digital promotions also prove eflective in driving interest and purchasing decisions. Thus, the optimisation of digital marketing strategies is an important key for companies to increase competitiveness and consumer loyalty in the midst of increasingly competitive business competition